(1 - 2x)⁴
(1 - 2x)(1 - 2x)(1 - 2x)(1 - 2x)
[1(1 - 2x) - 2x(1 - 2x)][1(1 - 2x) - 2x(1 - 2x)]
[1(1) - 1(2x) - 2x(1) - 2x(-2x)][1(1) - 1(2x) - 2x(1) - 2x(-2x)]
(1 - 2x - 2x + 4x²)(1 - 2x - 2x + 4x²)
(1 - 4x + 4x²)(1 - 4x + 4x²)
1(1 - 4x + 4x²) - 4x(1 - 4x + 4x²) + 4x²(1 - 4x + 4x²)
1(1) - 1(4x) + 1(4x²) - 4x(1) - 4x(-4x) - 4x(4x²) + 4x²(1) - 4x²(4x) + 4x²(4x²)
1 - 4x + 4x² - 4x + 16x² - 16x³ + 4x² - 16x³ + 16x⁴
1 - 4x - 4x + 4x² + 16x² + 4x² - 16x³ - 16x³ + 16x⁴
1 - 8x + 24x² - 32x³ + 16x⁴
Answer:
it is a 30 degree angle
Step-by-step explanation:
Answer:
The maximum revenue is 16000 dollars (at p = 40)
Step-by-step explanation:
One way to find the maximum value is derivatives. The first derivative is used to find where the slope of function will be zero.
Given function is:
![R(p) = -10p^2+800p](https://tex.z-dn.net/?f=R%28p%29%20%3D%20-10p%5E2%2B800p)
Taking derivative wrt p
![\frac{d}{dp} (R(p) = \frac{d}{dp} (-10p^2+800p)\\R'(p) = -10 \frac{d}{dp} (p^2) +800 \ frac{d}{dp}(p)\\R'(p) = -10 (2p) +800(1)\\R'(p) = -20p+800\\](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdp%7D%20%28R%28p%29%20%3D%20%5Cfrac%7Bd%7D%7Bdp%7D%20%28-10p%5E2%2B800p%29%5C%5CR%27%28p%29%20%3D%20-10%20%5Cfrac%7Bd%7D%7Bdp%7D%20%28p%5E2%29%20%2B800%20%5C%20frac%7Bd%7D%7Bdp%7D%28p%29%5C%5CR%27%28p%29%20%3D%20-10%20%282p%29%20%2B800%281%29%5C%5CR%27%28p%29%20%3D%20-20p%2B800%5C%5C)
Now putting R'(p) = 0
![-20p+800 = 0\\-20p = -800\\\frac{-20p}{-20} = \frac{-800}{-20}\\p = 40](https://tex.z-dn.net/?f=-20p%2B800%20%3D%200%5C%5C-20p%20%3D%20-800%5C%5C%5Cfrac%7B-20p%7D%7B-20%7D%20%3D%20%5Cfrac%7B-800%7D%7B-20%7D%5C%5Cp%20%3D%2040)
As p is is positive and the second derivative is -20, the function will have maximum value at p = 40
Putting p=40 in function
![R(40) = -10(40)^2 +800(40)\\= -10(1600) + 32000\\=-16000+32000\\=16000](https://tex.z-dn.net/?f=R%2840%29%20%3D%20-10%2840%29%5E2%20%2B800%2840%29%5C%5C%3D%20-10%281600%29%20%2B%2032000%5C%5C%3D-16000%2B32000%5C%5C%3D16000)
The maximum revenue is 16000 dollars (at p = 40)
-8
f(-1/2)=10(-1/2)-3
f(-1/2)=(-5)-3
f(-1/2)=-8
Answer:
8^4
Step-by-step explanation:
Here we have:
8^6 · 8³
-------------
8^5
That's multiplication in the numerator. The appropriate rule of exponents states that:
8^a·8^b = 8^(a+b), so the numerator is equivalent to 8^(6 + 3) = 8^9.
Now we have
8^9
------
8^5
and the appropriate rule for division here is
8^a / 8^b = 8^(a - b)
So our:
8^9
--------- 8^(9-5) = 8^4
8^5